(untitled) - Richards, Jack C. (New York, 2006)
Tune In develops listening skills and, introduces students to over 50 features of natural spoken English. Each lesson uses a step-by-step approach to teach students to understand what people say and how they say it. Students learn techniques such as how to check understanding, express uncertainty, and give polite negative answers. Easy-to-check material allows the teacher to focus on teaching rather than preparing.
Keywords: English language,Listening,Tiếng Anh thực hành,Kỹ năng nghe